1997
DOI: 10.1007/bf03189795
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium isotope effects on caffeine metabolism

Abstract: The aim of this work was to study the influence of labelling on caffeine metabolism according to the incubation mode. It has been observed that labelling induces an isotopic effect on metabolisation speed: apparent half-lives are systematically increased. Moreover, isotopic effects are in agreement with those previously observed for retention times. Qualitatively, caffeine labelling systematically induces metabolic variations to the detriment of the metabolic pathway that induces the loss of the trideuterometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Measurement of BK using a deuterated internal standard was performed using the peak area. This approach exploits the concept of parallelism, when chemically identical compounds differing in isotopic composition are characterized by the same retention time and are co-eluted within the defined peak borders Taking into consideration previous reports on differences in chromatographic mobility of deuterated and non-deuterated compounds, [35,[38][39][40] we additionally examined the value of the chromatography peak width at half maximum (w h ) of deuterated BK and native BK in an equilibrium mixture at low (1pg/mL), moderate (100 pg/mL) and high (1000 pg/mL) concentrations within the linear range. We found that at low concentration the chromatography peak widths of deuterated and native BK were almost indistinguishable and comparable (w h This phenomenon observed only at high concentrations possibly reflects a common feature of low molecular weight deuterated organic compounds (as compared to their natural hydrogenated counterparts).…”
Section: Influence Of Biological Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of BK using a deuterated internal standard was performed using the peak area. This approach exploits the concept of parallelism, when chemically identical compounds differing in isotopic composition are characterized by the same retention time and are co-eluted within the defined peak borders Taking into consideration previous reports on differences in chromatographic mobility of deuterated and non-deuterated compounds, [35,[38][39][40] we additionally examined the value of the chromatography peak width at half maximum (w h ) of deuterated BK and native BK in an equilibrium mixture at low (1pg/mL), moderate (100 pg/mL) and high (1000 pg/mL) concentrations within the linear range. We found that at low concentration the chromatography peak widths of deuterated and native BK were almost indistinguishable and comparable (w h This phenomenon observed only at high concentrations possibly reflects a common feature of low molecular weight deuterated organic compounds (as compared to their natural hydrogenated counterparts).…”
Section: Influence Of Biological Matrixmentioning
confidence: 99%
“…We found that at low concentration the chromatography peak widths of deuterated and native BK were almost indistinguishable and comparable (w h This phenomenon observed only at high concentrations possibly reflects a common feature of low molecular weight deuterated organic compounds (as compared to their natural hydrogenated counterparts). The effect of chromatographic isotopic separation can be explained by the fact that deuterated compounds are less lipophilic than the corresponding unlabeled compounds [39][40][41] because deuterium atoms are more electropositive than hydrogen atoms. Such chromatographic separation of isotopes is more evident for small organic compounds [40] and not so obvious for peptides.…”
Section: Influence Of Biological Matrixmentioning
confidence: 99%
“…Nonetheless, this consideration is valid for fully perdeuterated reagents or molecules in which a selective excitation of the pH 2 protons (without exciting other protons) is possible. The protonated and partially protonated precursor will be favorable to save costs when new compounds are synthesized for testing or when a kinetic isotope effect is to be avoided [70,71] . In such cases, the presented SOT schemes will be particularly advantageous, as undesired 1 H‐ 1 H J‐couplings are refocused.…”
Section: Figurementioning
confidence: 99%
“…Cette micro-production de gaz ne peut être directement quantifiée avec la grande précision qu'impose l'expérimentation. On fait alors appel au principe, un peu particulier, de la dilution isotopique inverse [2]. CO 2 can be produced by a lot of metabolic reactions and is the end point of numerous metabolisms.…”
Section: Principe De La Dilution Isotopique Inverseunclassified